Participation of Scheduled Castes Children at the Primary Stage in India - Tailor, Rajesh; Sharma, Sandeep Kumar; Tailor, Ritesh (JOURNAL OF INDIAN EDUCATION, 2007)
This paper discusses the participation of Scheduled Castes children at primary stage of school education in India according to Seventh All India School Education Survey (7th AISES). Among Scheduled Castes children, girls participation is specially focused. Present status has been compared with past data to know the improvement in their participation and it is statistically analysed. This paper will provide the base for the assessment of the development of educational status of Scheduled Castes children at primary stage of education after Sarva Shiksha Abhiyan (SSA) as the commencement year of SSA programme and year of information collection under Seventh All India School Education Survey is same.